2018
DOI: 10.12932/ap-160817-0137
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergen sensitization among 15,534 patients with suspected allergic diseases in Henan Province, China

Abstract: Background: The prevalence of allergen sensitization varies in different geographic areas and population subsets. This study investigated the prevalence and distribution of inhaled and food allergens among allergic patients in Henan Province, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
(21 reference statements)
2
10
0
1
Order By: Relevance
“…Los alimentos de origen animal con mayor sensibilización en nuestro estudio fueron huevo, camarón, leche de vaca, pescado, pollo y res; se ha descrito que el huevo y la leche de vaca son alimentos que incrementan el riesgo de desarrollar asma, 20 estos alimentos son frecuentes en la dieta de nuestra población y concuerda con resultados obtenidos en Pakistán, 21 Irán 22 y China, 23 donde se aprecia un patrón similar en la presencia de esos alimentos aunque con diferente frecuencia, sobre todo en adolescentes y adultos. En África se ha encontrado 9 % de alergia alimentaria principalmente a huevo (7 %) y se sugiere que el entorno rural es un factor protector importante para enfermedades alérgicas y alergia alimentaria.…”
Section: Discussionunclassified
“…Los alimentos de origen animal con mayor sensibilización en nuestro estudio fueron huevo, camarón, leche de vaca, pescado, pollo y res; se ha descrito que el huevo y la leche de vaca son alimentos que incrementan el riesgo de desarrollar asma, 20 estos alimentos son frecuentes en la dieta de nuestra población y concuerda con resultados obtenidos en Pakistán, 21 Irán 22 y China, 23 donde se aprecia un patrón similar en la presencia de esos alimentos aunque con diferente frecuencia, sobre todo en adolescentes y adultos. En África se ha encontrado 9 % de alergia alimentaria principalmente a huevo (7 %) y se sugiere que el entorno rural es un factor protector importante para enfermedades alérgicas y alergia alimentaria.…”
Section: Discussionunclassified
“…In Asia, peanut allergy prevalence seems to be low compared to US and certain western countries (76,(89)(90)(91)(92). Cashew nut is one of the most common reported tree nuts causing allergy in Asia (67,70,71,74). However, tree nut allergy prevalence varies significantly across Asia especially between East and Southeast Asia and the Middle East (62,63,66,70,74).…”
Section: Walnutmentioning
confidence: 99%
“…4,[12][13][14] The mite mixed (Dermatophagoides pteronyssinus and Dermatophagoides farina) were the most common aeroallergen sensitization in Chinese and Hong Kong, respectively, [Henan Province (22.8%) and Hong Kong (63.0%)]. 9,12 In Thailand, the mite mixed was the most common aeroallergen sensitization (range from 50.1% to 62.2%). 4,13 However, these studies were conducted in Bangkok and Phra Nakhon Si Ayutthaya Province located in central part of Thailand.…”
Section: Introductionmentioning
confidence: 99%
“… 7 The previous studies showed that the prevalence of AR defined by positive SPT range from 9% to 42%. 8 , 9 The prevalence of aeroallergen sensitization varies in different regions and countries. Cat and cedar pollen were the most common aeroallergen sensitization in Sweden and Japan, respectively.…”
Section: Introductionmentioning
confidence: 99%